Effects of mulching with different specifications of plastic film on the growth of fresh-eating maize (Bangladesh Journal of Botany, 2025)
This study examines the effects of plastic film mulching with varying specifications on the mid-to-late growth stages of fresh-eating maize, analyzing differences in weed growth, leaf length, plant height, growth period and yield. The findings reveal that black plastic film effectively suppresses weed growth, whereas white plastic film fosters it. Prior to the trumpet stage, white plastic film demonstrates a superior ability to enhance leaf elongation compared to black plastic film. However, after entering the trumpet stage, black plastic film proves more advantageous. Based on variations in leaf color under different mulching treatments, it can be inferred that black plastic film significantly increases chloroplast quantity or chlorophyll content, thereby promoting photosynthesis and overall growth. Maize plants exhibit a marked increase in height with black plastic film, with thickened black film yielding the most pronounced effect, while white plastic film hinders height growth. Additionally, black plastic film enhances the number of ears per plant and ear length, with thickened black film yielding the best results. Mulching cultivation also has a positive impact on the number of kernel rows per ear, with black plastic film exhibiting a more significant effect than white plastic film.Bangladesh J. Bot. 54(3): 761-768, 2025 (September) Special